Kajian Literatur: Efektivitas Perencanaan Pembelajaran Sejarah Berbasis Problem Based Learning (PBL) dalam Mengembangkan Kemampuan Berpikir Kritis Siswa - Mukhlisin Nata Hudin; Arina Asmal Hidayah; Vivi Widia Wati; Sani Safitri; Rani Oktapiani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This literature review examines the effectiveness of planning history learning based on the Problem Based Learning (PBL) model in developing students critical thinking skills. The study is motivated by the persistent dominance of teacher-centered instruction in history classes, which limits students analytical and reflective engagement with historical issues. This research aims to analyze how structured PBL, based lesson planning especially in designing problems, learning activities, media, and evaluation tools. Can enhance critical historical reasoning. Using a qualitative descriptive method through a review of journal articles, books, and research reports, the study finds that effective PBL planning requires identifying authentic historical problems, organizing collaborative inquiry activities, providing adequate scaffolding, and using critical thinking oriented evaluation rubrics. The results show that PBL consistently improves students’ analytical, evaluative, and interpretive abilities when supported by systematic planning and sufficient learning resources. The study implies that teachers must strengthen the planning phase, particularly in preparing learning scenarios and assessment instruments, to maximize the impact of PBL on critical thinking development.